Microwave Assisted Rapid, Efficient and Chemoselective Deoxygenation of Sulfoxides to Thioethers Using Zn / AcOH on Silica Gel - Abbas Shockravi; Esmael Rostami; Davood Heidaryan; Hanif Fattahi (Iranian Journal of Chemistry & Chemical Engineering, 2008)
Zn/AcOH on silica gel converts a range of structurally different sulfoxides to their corresponding thioethers in excellent yields under microwave irradiation. It has been found that chemoselective deoxygenation of sufoxides can be achieved in the presence of other reducible functional groups such as acetals, acids, amides,   esters, ketones and nitriles.